2022
DOI: 10.1038/s41574-022-00773-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic determinants of tumour initiation

Abstract: Tumours exhibit notable metabolic alterations compared with their corresponding normal tissue counterparts. These metabolic alterations can support anabolic growth, enable survival in hostile environments and regulate gene expression programmes that promote malignant progression. Whether these metabolic changes are selected for during malignant transformation or can themselves be drivers of tumour initiation is unclear. However, intriguingly, many of the major bottlenecks for tumour initiation -control of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 213 publications
2
12
0
Order By: Relevance
“…Moreover, leukemic stem cells derived from CML patients relied on upregulated oxidative metabolism for their survival [ 171 ]. Similar observations have been made with stem cells of other tumor types (reviewed in [ 172 ]). Mitochondrial respiration was also found to be essential for tumorigenesis in a KRAS-driven mouse model of lung cancer through the generation of ROS, which were required for the MAPK signaling-dependent induction of anchorage-independent growth [ 173 ].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, leukemic stem cells derived from CML patients relied on upregulated oxidative metabolism for their survival [ 171 ]. Similar observations have been made with stem cells of other tumor types (reviewed in [ 172 ]). Mitochondrial respiration was also found to be essential for tumorigenesis in a KRAS-driven mouse model of lung cancer through the generation of ROS, which were required for the MAPK signaling-dependent induction of anchorage-independent growth [ 173 ].…”
Section: Discussionsupporting
confidence: 83%
“…Alignment of CST sequences from 53 mammalian species belonging to eight orders revealed that CST sequence is highly conserved (>90% in 90% species) in mammals: Five (23.8%) amino acids (M 3 , L 5 , F 7 , F 14 , and G 18 ) are 100% conserved; nine (42.8%) amino acids (S 2 , K 4 , S 6 , R 8 , R 10 , R15, P17, Q20 and L21) are 90-96% conserved; and three (14.28%) amino acids (A9, A11, and G16), are >80% conserved. The least conserved sequences are G13 (>66%) and P19 (>58%), where human variants of CST were reported for G13 (G13S) and P19 (P19L), indicating that natural selection pressures still exist on those two amino acids [195][196][197][198]. Existing literature (expression of CST in innate immune cells, inhibition of macrophage infiltration in tissues, decreased expression of pro-inflammatory cytokines by CST, and low plasma CST in fatal COVID-19 patients) implicate CST as an immunomodulatory peptide.…”
Section: Discussionmentioning
confidence: 99%
“…One instance of cancer-associated metabolic reprograming with a significant role in cancer is the shift to aerobic glycolysis driven by mutation of metabolic enzymes, such as the TCA cycle enzyme FH. This change results in altered cellular metabolite levels, which affect cellular signaling and gene expression (21). The shift in metabolism driven by loss of FH activity generates an inhibitory environment for enzymes in the 2OGDD family.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes in this family catalyze hydroxylation reactions on lipids, proteins, and nucleic acids (19). Critically, the activity of these enzymes is dependent upon the availability of iron, oxygen, and the ratio of αKG to related TCA cycle metabolites such as succinate and fumarate (20,21). Aberrant accumulation of 2HG, succinate, or fumarate 1 can disrupt the activity of 2OGDDs, leading to changes in gene expression programs and promoting tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%